Maximal power output. Training and design variables for performance enhancement - Jordan, M. (High Performance SIRCuit, 2010)
Power is defined mathematically as the work produced per unit of time and is measured in Watts (W). The power equation can also be written as the product of force and velocity (i.e. Power = Force x Velocity). Scientific investigations and practical experience have revealed maximal power output is an important strength quality for many sports. Not only is the maximal power production critical for shorter more sprint orientated events but it is also important for endurance athletes, as improving maximal power output can positively affect economy of motion. Interestingly, maximal power is also positively associated with functionally for the elderly. In layman's terms, power is the ability to produce muscular force quickly and this stength quality is extremely important for health and athletic performance.